Efficacy and safety of fezolinetant and its different doses in the treatment of vasomotor symptoms in menopausal women: a systematic review and meta-analysis - Rahma Abdelaziz Ismail; Rahma Sameh Shaheen; Eslam Afifi; Reem Sayad; Leenah N. Sherif; Mohamed Ibrahim Aranda; Rawda A. Al Gohary; Ahmed Saad Elsaeidy (Middle East Fertility Society Journal)
Abstract Introduction Fezolinetant, an oral NK3R antagonist, selectively blocks NKB signaling, improving vasomotor symptoms by reducing KNDy neuron activity. Our review assesses fezolinetant’s efficacy and safety in treating VMSs in menopausal women. Methods We conducted a systematic review and meta-analysis synthesizing randomized controlled trials, which were retrieved by systematically searching PubMed, Scopus, Web of Science, Cochrane, Embase, MEDLINE, Ovid full text, and CINAHL until May 2023. We used RevMan V. 5.4 to pool dichotomous data using risk ratio and continuous data using the mean difference with a 95% confidence interval. Results We included eight studies from seven RCTs. Fezolinetant showed significant efficacy in reducing the frequency of vasomotor symptoms in menopausal women, with a mean difference reduction of 1.96 episodes per day (95% CI [− 2.48, − 1.45], P < 0.00001). Additionally, women in the fezolinetant group were more likely to acquire a reduction of at least 70% from baseline in VMS frequency (OR = 2.22, 95% CI [1.55, 3.18]: P < 0.0001). Fezolinetant also showed significant efficacy in reducing the VMS severity after 12 weeks (MD = − 0.18, 95% CI [− 0.26, − 0.10], P < 0.0001). Quality of life measures also favored fezolinetant, showing a significant reduction in MENQOL score by 0.32 points (95% CI [− 0.52, − 0.13], P = 0.0009). Importantly, fezolinetant exhibited a favorable safety profile, with no significant difference in liver test elevations compared to placebo after 12 weeks (OR = 1.00, 95% CI [0.68, 1.47], P = 0.99). It also exhibited no statistically significant difference in treatment-emergent adverse events after 12 weeks by different doses (30, 45, and 180 mg). Conclusion Fezolinetant demonstrated significant efficacy in reducing VMS frequency and severity and improving quality of life. Safety outcomes revealed no significant differences in liver safety assessments or treatment-emergent adverse events compared to placebo. Trial registration PROSPERO CRD42023484019.